NON-DIGITAL FACTORS AS A PREREQUISITE FOR THE IMPLEMENTATION OF SEAPORT DIGITALIZATION THROUGH BIBLIOMETRIC ANALYSIS - AUTSADEE, YUTHANA; JEEVAN, JAGAN; MOHD SALLEH, NURUL HAQIMIN; SANGSAWANG, CHATNUGROB; POMA, WORAWUT (Journal of Maritime Logistics, 2023)
This research conducts a comprehensive exploration of the prerequisites involved in seaport digitalization through a rigorous bibliometric analysis, with a specific focus on non-digital factors. The study reveals critical insights into the landscape of seaport digitalization, emphasizing the foundational role of effective leadership and stakeholder engagement in fostering innovation and alignment with the diverse needs of the maritime community. Strategic planning emerges as pivotal, providing a purposeful digital transformation journey with clear vision and goals. A robust technology infrastructure, encompassing IT systems, cloud computing, and cybersecurity, positions seaports for adaptability and technological leverage. Effective data management, workforce training, and compliance with regulations are identified as paramount for digitalization success. Despite these contributions, the study acknowledges limitations in the bibliometric analysis and emphasizes the dynamic nature of technology. Recommendations for future research include in-depth regional studies, longitudinal analyses, comparative studies, exploration of human-centric aspects, and investigations into emerging technologies. While offering valuable insights, this research advocates for continued exploration into specific aspects and regional nuances in the dynamic field of seaport digitalization.